Utilizing Cooperative Integrated Reading and Composition (CIRC) with mobile Learning to Enhance Students' Reading Comprehension - Nirwanto Maruf; A. Maya Rupa Anjely (British : Jurnal Bahasa dan Sastra Inggris, 2020)
This present study aims to find out the how significant the utilization of Cooperative Integrated Reading and Composition (CIRC) with mobile learning on students’ reading comprehension. This study is conducted by using the quantitative method with pre-experimental design.  The instrument used in in this study was test sheet called as Reading Comprehension Test (RCT), and it employed in pre-test and post-test, it was developed and selected from student textbooks, story books, and authentic materials to measure students’ reading comprehension achievement. The present results reveal that CIRC teaching strategy with mobile learning (m-learning) improved students’ performance in reading comprehension, it was indicated from the result of paired samples test (t-test) that the value of the t-observed significant is at .000 is lower than .050 (.000 < .050, this means students’ improvement is significant after exposed by the experimentation (treatment) process. Based on the result, it concluded that the utilization of Cooperative Integrated Reading and Composition (CIRC) with mobile learning as teaching strategy can enhance students’ reading comprehension.Keywords: Cooperative Integrated Reading and Composition (CIRC), Mobile Learning, Reading Comprehension.